1998
DOI: 10.1046/j.1365-2958.1998.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

ClpX and ClpP are essential for the efficient acquisition of genes specifying type IA and IB restriction systems

Abstract: SummaryEfficient acquisition of genes that encode a restriction and modification (R-M) system with specificities different from any already present in the recipient bacterium requires the sequential production of the new modification enzyme followed by the restriction activity in order that the chromosome of the recipient bacterium is protected against attack by the restriction endonuclease. We show that ClpX and ClpP, the components of ClpXP protease, are necessary for the efficient transmission of the genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 47 publications
0
50
0
Order By: Relevance
“…These experiments implicated the protease ClpXP (Makovets et al, 1998), which comprises two components, ClpX and ClpP. In the absence of either ClpX or ClpP, acquisition of hsd genes specifying either EcoKI (type IA) or EcoAI (type IB) led to the death of modification-deficient recipients (Makovets et al, 1998). Together, ClpX and ClpP form a large, but hollow, complex (see Gottesman, 1999) ; ClpX serves to recognize and unfold its substrate so that the polypeptide can be transported to the chamber within the complex where it becomes the target for degradation by ClpP.…”
Section: Clpx and Clpp Are Needed To Modulate The Restriction Activitmentioning
confidence: 94%
See 4 more Smart Citations
“…These experiments implicated the protease ClpXP (Makovets et al, 1998), which comprises two components, ClpX and ClpP. In the absence of either ClpX or ClpP, acquisition of hsd genes specifying either EcoKI (type IA) or EcoAI (type IB) led to the death of modification-deficient recipients (Makovets et al, 1998). Together, ClpX and ClpP form a large, but hollow, complex (see Gottesman, 1999) ; ClpX serves to recognize and unfold its substrate so that the polypeptide can be transported to the chamber within the complex where it becomes the target for degradation by ClpP.…”
Section: Clpx and Clpp Are Needed To Modulate The Restriction Activitmentioning
confidence: 94%
“…It has been shown that the bacterial chromosome becomes susceptible to restriction as cell growth dilutes the modification enzyme (Handa et al, 2000). However, while the loss of genes that specify some simple R-M systems leads to cell death, the loss of genes that specify other, more complex, R-M systems causes no detectable viability problem (O'Neill et al, 1997 ;Kulik & Bickle, 1996 ;Makovets et al, 1998). In this by EcoKI and thus forms plaques with reduced efficiency (e.o.p.…”
Section: Background and Aimsmentioning
confidence: 99%
See 3 more Smart Citations